The Cambridge encyclopedia of India, Pakistan, Bangladesh, Sri Lanka, Nepal, Bhutan and Maldives (Cambridge, New York, 1989)
The book offers for the first time a comprehensive study of South Asia and analyzes not just the riches of the past but also the problems and achievements of the present. South Asia region, which comprises the present-day states of India, Pakistan, Bangladesh, Sri Lanka, Nepal, Bhutan and the Maldives, has long been significant in world affairs. The first two parts of the book - Land and Peoples - introduce both the geography of the region, including essays on water resources, wildife and disasters, and the many diffeent peolples, discussiing amongs other things major issues in demography, urbanization and migration. The third part covers History from the Indus Vallay civilization to the end of British rule including the separate experiences of the Himalayan kingdoms. The fourth examines the modern politics of every state, in the case of India analyzing the workings of the world largest democracy in depth. Part V studies the relationships between the states of the region, and those of India and Pakistan with international politics. Economies examines the main problems of the development and the performance of South Asia states in agriculture, energy supply, trade, industry, communications, savings nd investment. The section on Religions studies the many ways South Asians have found to make sense of life, focusing not just on the old way but also on the vigorous revivals that several religions have experienced in recent times. The section on Societies shows how the encounter with the West and the growth of the modern state have raised new ways of living, new forms of law, knowledge, welfare provision, and even sports and games, to exist side by side with, and to interact with, the traditional forms of the region. The final part surveys in great detail South Asia's wealth of cultural expression. The literatures of twenty-three different languages are studied; so are classical and popular music, and classical and folk dance; so too are architecture, sculpture, painting and the decorative art, care being taken to note the cross-fertilization of local and high cultural traditions. There are also essays on food, dress, publishing, the media, science and technology, and most notably the cinema, India's dominant modern art form of worldwide reputation. The book is richly illustrated with many photographs, maps and tables, closely interwoven with the text
Keywords: south asia - dictionaries and encyclopedias,south asia, social conditions